Analysis of pulsed laser diode driver system for multistate quantum key distribution - Abdullah M.S.; Jamaludin M.Z.; Witjaksono G.; Mokhtar M.H.H. (2023)
In this paper, we analyse a pulsed laser diode driver system based on MOSFET current mirror and digital signal controller (DSC) designed to emit stream pairs of photons from three semiconductor laser diodes. The DSC is capable to switch between the three laser diodes at constant rate. The duty cycle is maintained at below than 10% while the pulse width of the modulation current is set at around 30ns in order to minimize its thermal effect and thus prolong the laser diodes life cycle. The MOSFET current mirror circuits are capable of delivering constant modulation current to the laser diodes with its peak is up to 58mA resulting a peak optical power output around 7dBm. 2010 IEEE.